Comparison of Isometric Hand Grip Strength among Computer Operators and Non-Computer Operators - Hiba Sultan, Saman Babar, Momin Mukhtar, Umair Abu Bakar Siddiq, S. Javaid Ahmad, Mahnoor Shafiq, Alisha Ehsan, M. Haris (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Most frequently self-reported work-related illness are due to musculoskeletal disorders. Highly repetitive tasks with grasping of the hands, repetitive flexing of the wrist, vibrations and localized mechanical pressure play a role in development of repeated stress injury. Many computer users complain about wrist fatigue, discomfort or pain after typing. Aim: To assess and compare isometric grip strength of computer operators and non-computer operators. Methods: This study was conducted at the Shalimar Institute of Health Sciences. A sample of 30 computer operators and 30 controls (non-computer operators) were recruited after screening hand ultrasonography. Purposive sampling was used. Isometric grip is measured with a hand-held dynamometer. Subjects were asked to hold the dynamometer with full exertion. Each reading is from a maximum contraction period of three seconds with a 30-second pause. Results: Average Hand Grip Strength of computer operators was 27.71±11.19kg and non-computer users was 37.05±11.09kg. The results were statistically significant with the p-value of 0.002. Practical Implications: Continuous computer use reduces hand grip strength therefore those who are having long term use of computers must go for hand grip strength exercises to maintain normal hand grip strength. Conclusion: Computer operators have less isometric hand grip strength than non-computer operators as it was concluded in this study. MeSH words: Isometric hand grip strength, computer operators, non-computer operator